Makam Kuno Sebagai Tempat Ziarah Di Pulau Barrang Lompo Ancient Tombs as Pilgrimage Sites on Barrang Lompo Island - Husnul Khotimah Am; Tri Putri Yati; Natasya Natasya (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2026)
This study aims to understand the role of ancient tombs on Barang Lompo Island as pilgrimage sites, focusing on three main aspects: spiritual, social, and economic. To achieve these objectives, the study was conducted qualitatively using descriptive methods, through literature review from various sources such as journals, articles, and related publications. The results show that ancient tombs on Barang Lompo Island function as spiritual centers for pilgrims seeking blessings, inner peace, and religious experiences. From a social perspective, the pilgrimage tradition helps strengthen social relations in the surrounding community and serves as a means of transmitting cultural and historical values. Meanwhile, economically, the presence of many visitors has created new business opportunities for local residents, such as selling souvenirs, providing guide services, and renting out accommodations. However, the increasing number of visitors also brings challenges in terms of maintaining environmental cleanliness and maintaining the authenticity of the pilgrimage site.